Evaluation of the Implementation of Occupational Safety and Health (K3) in the Road Improvement Construction Project in Kabanjahe, Karo Regency - Theo Haganta; Mardiaman; Hikma Dewita (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2025)
Road construction projects are among the sectors with a high risk of work-related accidents. One of the main causes is the low awareness and compliance of workers in using Personal Protective Equipment (PPE), which should be an integral part of Occupational Safety and Health (OSH) implementation. This study aims to evaluate the implementation of OSH, particularly regarding the use of PPE, in a road improvement project in Kabanjahe District, Karo Regency. The method used is a quantitative approach through questionnaires distributed to 140 field workers. The analysis results show that factors such as lack of education on PPE, weak supervision by management, substandard PPE quality, and a work culture that neglects safety are the main reasons for low compliance. The most influential factors include lack of awareness of work safety importance and absence of routine training related to OSH. Therefore, an integrated strategy is needed, which includes intensive education, provision of PPE that meets national standards (SNI), as well as strict supervision and enforcement, to ensure optimal OSH implementation and reduce the number of work accidents in construction projects.